Draft Annual Plan 1971-72 Part-I Explanatory Memorandum Government of Tripura - Planning Commission (Planning Commission, 1971)
The climate is generally hot and. humid with temperature ranging from 8.9°c and 42°c. Normal rainfall in this Territory is about 2100.7 mm. The soil is laterite with little water absorption capacity. The flat land in the valleys is alluvial consisting of Sand, Silt and Clay. About 60% of the total area is hilly land. The remaining 40% constitute flat lands and accommodate about two-third of the population.
Government of Tripura, Development (Planning and Coordination) Department